2014
DOI: 10.1002/ppap.201400047
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Silicon Nanostructures by Atmospheric Microplasma Jet: The Role of Hydrogen Admixture

Abstract: International audienceSilicon nanostructures are synthesized with a DC atmospheric pressure microplasma jet using an Ar/SiH4/H-2 gas mixture. The plasma is characterized by OES and imaged using an EMCCD camera. The effect of hydrogen admixture to the formed structures is studied by transmission electron microscopy. Under specific conditions, crystalline silicon nanoparticles grow in an amorphous matrix investigated by electron energy loss spectroscopy. As-grown silicon nanoparticles are collected in ethanol fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 24 publications
0
18
1
Order By: Relevance
“…Up to now, extensive investigations have been carried out on the synthesis and study of the optical properties of colloidal silicon nanoparticles in ethanol. It has been shown that the excitationdependent visible emissions of colloidal SiNPs in ethanol is mainly originated from the quantum confinement effect and surface chemistry of the alkyl-passivated SiNPs [10][11][12][13][14][46][47][48]. However, our observations reveal that the colloidal SiNPs in ethanol exhibits similar PL behaviour to the pure ethanol at the spectral range of 300-600 nm, with a slight enhancement of PL intensity.…”
Section: Introductioncontrasting
confidence: 71%
See 1 more Smart Citation
“…Up to now, extensive investigations have been carried out on the synthesis and study of the optical properties of colloidal silicon nanoparticles in ethanol. It has been shown that the excitationdependent visible emissions of colloidal SiNPs in ethanol is mainly originated from the quantum confinement effect and surface chemistry of the alkyl-passivated SiNPs [10][11][12][13][14][46][47][48]. However, our observations reveal that the colloidal SiNPs in ethanol exhibits similar PL behaviour to the pure ethanol at the spectral range of 300-600 nm, with a slight enhancement of PL intensity.…”
Section: Introductioncontrasting
confidence: 71%
“…Up to now, extensive investigations have been carried out on synthesis and studying of the optical properties of colloidal silicon nanoparticles in ethanol and other organic solvents. It has been reported that the excitation-dependent emission properties of colloidal SiNPs in ethanol at the spectral range of 300-600 nm mainly originated from the quantum confinement effect and surface chemistry of the alkylpassivated SiNPs [10][11][12][13][14][46][47][48]. However, our observations reveal that the excitation-dependent PL spectra of the colloidal SiNPs in ethanol (at the spectral range of 300-600 nm) are associated with the Raman scattering of pure ethanol which are enhanced due to the presence of SiNPs with different OH related surface characteristics.…”
Section: Resultsmentioning
confidence: 99%
“…Nucleation, growth, and nanoparticle heating are mechanisms closely related in APPs. Although further confirmation will be required, nucleation in APPs appears to take place via super‐saturation of silicon atoms rather than through a polymerization process of SiH x radicals as observed in low‐pressure plasmas; this is partly supported by strong emission of atomic silicon lines in silane‐based APPs . Therefore full silane dissociation is necessary in APPs to achieve crystalline Si QDs.…”
Section: Photovoltaic Materials By Atmospheric Pressure Plasmasmentioning
confidence: 99%
“…Atmospheric pressure microplasmas are very versatile tools to control the composition and crystallinity of Si‐based QDs . Nucleation, growth, and nanoparticle heating are mechanisms closely related in APPs.…”
Section: Photovoltaic Materials By Atmospheric Pressure Plasmasmentioning
confidence: 99%
“…Nanocrystals can be synthesized in a variety of plasma reactors [22][23][24][25][26][27][28][29]. In one example, developed in the author's group [10], a precursor gas diluted in a carrier gas such as argon or helium passes through a reactor tube with a relatively high flow velocity, Fig.…”
Section: Nanocrystal Synthesismentioning
confidence: 99%